ANALISIS POTENSI LIMBAH TULANG AYAM DAN IKAN DARI PKL SEBAGAI SUMBER MINERAL KALSIUM FOSFAT - Nasution, Ahmad Kafrawi; Permata, Ekie Gilang (Sistem Informasi, 2016)
This study aimed to find out how much potential waste from chicken bones and fish collected from street vendors in the city of Pekanbaru to pulverized bone and mineral calcium phosphate nanoparticle size. This research is motivated by many vendors who are considered disturbing the aesthetics and cleanliness of the city. The research was conducted in the city of Pekanbaru by using primary data obtained from a survey of street vendors. While secondary data obtained from the Office of Market town of Pekanbaru, statistical data and the results of previous studies. Data samples are taken randomly from street vendors in the city of Pekanbaru based on the types of food sold as roasted chicken and fried catfish. The process of making bone powder are derived from chicken and fishbones through several stages. For bone drying process is done at a temperature of 100 OC for 15 minutes. As for the bone turnover process is performed at a temperature of 700 OC for 6 hours. The results showed that the huge potential of the waste bones if used as a source of mineral raw materials Calcium Phosphate. This research could also describe an increase in economic value if it produces powder bone and bone powder with the size of the nanoparticles.